Isolation, identification, phytochemical screening, and antibacterial activity of Aspergillus sp. MFD-01, an endophytic fungus derived from Mesua ferrea - Dwi Hartanti; Risda Yunita Andestia Sinaga; Asmiyenti Djaliasrin Djalil; Retno Wahyuningrum (Pharmaciana, 2018)
We have successfully isolated and identified endophytic fungi from medicinal plant Mesua ferrea L. grown at Banyumas were for the first time. One of those fungi was MFD-01. In this study, we report the isolation, identification, antibacterial activity, and phytochemical screening of Aspergillus sp. MFD-01. The endophytic fungus was isolated from the leaves of M. ferrea by subsequent inoculation on potato dextrose agar (PDA). The identification was based on its morphology and ITS-DNA sequence. The antibacterial activity was determined by dilution method. The identification of compounds in ethyl acetate extract of it was conducted according to the standart phytochemical screening method. MFD-01 was identified as Aspergillus sp. MFD-01. The ethyl acetate extract of Aspergillus sp. MFD-01 inhibited the growth of both Staphylococcus aureus, and Escherichia coli. At concentration of 1000 ppm, its diameter of inhibitory zone against those bacteria was 10.53 and 11.84, respectively. The extract contained flavonoids, alkaloids, saponins, terpenoids, and tannins, which might responsible for its antibacterial activity against both tested bacteria.